2021
DOI: 10.1038/s41598-021-96345-0
|View full text |Cite
|
Sign up to set email alerts
|

Population-based study on birth outcomes among women with hypertensive disorders of pregnancy and gestational diabetes mellitus

Abstract: To evaluate birth outcomes in women with hypertensive disorders of pregnancy (HDP) and gestational diabetes mellitus (GDM), we used insurance data of Taiwan to evaluate 11 adverse neonatal outcomes of infants born to women with HDP (N = 7775) and with both HDP and GDM (HDP/GDM) (N = 1946), comparing to women with neither disorder (N = 19,442), matched by age. The impacts of preeclampsia/eclampsia were also evaluated. Results showed that Caesarean section delivery was near 1.7-fold greater in the HDP/GDM and HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
3
8
1
Order By: Relevance
“…Similar to our study ndings, other studies have reported birth asphyxia as the leading cause of neonatal morbidity among neonates born of pre-eclamptic women owing to lung immaturity and insu cient surfactant production (21,22,29) . Previous studies have however reported con icting ndings on the impact of hypertension on birth asphyxia (30)(31)(32) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to our study ndings, other studies have reported birth asphyxia as the leading cause of neonatal morbidity among neonates born of pre-eclamptic women owing to lung immaturity and insu cient surfactant production (21,22,29) . Previous studies have however reported con icting ndings on the impact of hypertension on birth asphyxia (30)(31)(32) .…”
Section: Discussionsupporting
confidence: 92%
“…About two thirds 107(59.44%) of the LBW neonates were delivered via caesarean section owing to non-reassuring fetal status and worsening preeclampsia or impending eclampsia. The nding is congruent with other studies that have reported caesarian section as the most common mode of delivery among pre-eclamptic women in order to mitigate against adverse perinatal outcomes (21)(22)(23) . The mean APGAR scores for the participants were consistent with other studies that have reported low APGAR scores in LBW neonates at one and ve minutes compared to normal weight neonates [AOR = 0.52 (95%CI: 0.37-0.73), p ≤ 0.001] (24)(25)(26) .…”
Section: Discussionsupporting
confidence: 89%
“…Premature delivery is a common consequence of preeclampsia [ 35 ]. Premature birth is defined as a live birth at a gestational age < 37 weeks, when the neonatal organ systems are immature, which is one of the main reasons for the increased risk of perinatal and infant morbidity and mortality [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the rate of small-for-gestational-age (SGA) babies was greater in patients with HDP with and without GDM in comparison to the control group, with an adjusted OR of 6.57 (95% CI 5.56–7.75) and 5.81 (95% CI 5.15–6.55), respectively. The incidence of adverse outcomes increased further in women with PE and eclampsia [ 26 ]. Our results contradict these results, because in our research, the incidence of preterm birth and FGR was lower in patients with PE and coexisting GDM than in women with PE alone.…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, there is only one study referring to the impact of GDM on the course of pregnancy complicated by hypertensive disorders indicating an increased risk of adverse pregnancy outcomes in women with both gestational hypertension (GH) and GDM [ 26 ]. There is also another study comparing PE biomarkers in patients with PE alone, PE+GDM, GDM alone, and healthy controls demonstrating that sFlt-1 overproduction is also related to PE in GDM pregnancies, even though it is characterized by a less severe endothelial dysfunction [ 21 ].…”
Section: Introductionmentioning
confidence: 99%